Rapid Damage and Loss Assessment : November 9-11 and November 28, 2016 Floods - Government of Saint Vincent and the Grenadines (World Bank, Washington, DC, 2017)
In November 2016, two tropical trough systems produced heavy rains in Saint Vincent and the Grenadines, which resulted in intense flooding across the island chain. The torrential rains, ensuing flash flooding, and landslides resulted in widespread damage to road, bridges, water infrastructure, and housing. Our extreme vulnerability to natural disasters and the impacts of climate variability continues to be of grave concern. This ‘Saint Vincent and the Grenadines Rapid Damage and Loss Assessment, November 9–11 and November 28, 2016 Floods’ Report serves as a reminder and proof of the Government’s resolve and commitment to risk reduction as well as the well-being of our people. The Government recognizes the necessity to better understand our climate and disaster risk context and is continuing the battle to reduce this risk and improve resilience across all sectors. This report provides a rapid damage and loss assessment of the affected sectors, with focus on infrastructure damage to inform the Government’s recovery, reconstruction, and financial planning. It also includes short- and medium-term recommendations designed to further incorporate disaster risk reduction and management into land use and physical planning decision-making processes so that we continue to develop into a country that is more resilient to natural disasters and climate change.